2020
DOI: 10.1186/s40359-020-00415-3
|View full text |Cite
|
Sign up to set email alerts
|

How anxious is too anxious? State and trait physiological arousal predict anxious youth’s treatment response to brief cognitive behavioral therapy

Abstract: Background Exposure therapy is the gold standard for treating childhood anxiety, yet not all youth improve. Children do not always have insight on their distress, which can limit the utility of self-reported units of distress (SUDS) during exposures. Physiological assessment provides an objective means of monitoring emotional arousal. Electrodermal activity (EDA) in particular indexes sympathetic nervous system arousal which is heavily linked to anxiety. The aim of the current study was to examine the feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The studies were published between 2017 and 2023 and the majority were conducted in Europe [96,97,98,99,100] and the USA [101,102,103,104]. Most of the studies were pilot or feasibility studies, without randomization [96,97,98,99,100,102].…”
Section: Characteristics Of the Studies Included In The Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies were published between 2017 and 2023 and the majority were conducted in Europe [96,97,98,99,100] and the USA [101,102,103,104]. Most of the studies were pilot or feasibility studies, without randomization [96,97,98,99,100,102].…”
Section: Characteristics Of the Studies Included In The Reviewmentioning
confidence: 99%
“…The studies were published between 2017 and 2023 and the majority were conducted in Europe [96,97,98,99,100] and the USA [101,102,103,104]. Most of the studies were pilot or feasibility studies, without randomization [96,97,98,99,100,102]. Only 3 of the included studies were RCTs [110,112,113] and one pre-registration for an ongoing study could be identified via the "grey literature search" [105].…”
Section: Characteristics Of the Studies Included In The Reviewmentioning
confidence: 99%
See 3 more Smart Citations